The Constitution of the United States of America a contextual analysis - Tushnet, Mark V. 1945- (Constitutional systems of the world, 2009)
This book provides a critical introduction to the history and current meaning of the United States' Constitution. It is organised around two themes: Firstly, the U.S. Constitution is old, short, and difficult to amend. These characteristics have made constitutional 'interpretation', especially by the U.S. Supreme Court, the primary mechanism for adapting the Constitution to ever-changing reality. Secondly, the Constitution creates a structure of political opportunities that allows political actors, including political parties, to pursue the preferred policy goals even to the point of altering the very structure of politics. Politics, that is, often gives meaning to the Constitution. Deploying these themes to examine the structure of the national government, federalism, judicial review, and individual rights, the book provides basic information about, and deeper insights into, the way the U.S. constitutional system has developed and what it means today.